2009
DOI: 10.1016/j.annemergmed.2009.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of 30-Day Serious Events in Older Patients With Syncope

Abstract: Study objective: We identify predictors of 30-day serious events after syncope in older adults. Methods:We reviewed the medical records of older adults (age Ն60 years) who presented with syncope or near syncope to one of 3 emergency departments (EDs) between 2002 and 2005. Our primary outcome was occurrence of a predefined serious event within 30 days after ED evaluation. We used multivariable logistic regression to identify predictors of 30-day serious events.Results: Of 3,727 potentially eligible patients, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
97
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(102 citation statements)
references
References 38 publications
2
97
0
3
Order By: Relevance
“…4 Inclusion of patients with serious adverse events identified in the emergency department introduces bias in the tool (e.g., low hematocrit is identified as a risk factor if patients with obvious gastrointestinal bleeding in the emergency department were included, but it is no longer significant after exclusion of these patients). 9,13,28 In our study, we found predisposition to vasovagal syncope to be negatively associated with serious adverse events. The Evaluation of Guidelines in Syncope Study (EGSYS) score, developed to identify patients with cardiac syncope, reported a similar finding.…”
Section: Discussionmentioning
confidence: 69%
“…4 Inclusion of patients with serious adverse events identified in the emergency department introduces bias in the tool (e.g., low hematocrit is identified as a risk factor if patients with obvious gastrointestinal bleeding in the emergency department were included, but it is no longer significant after exclusion of these patients). 9,13,28 In our study, we found predisposition to vasovagal syncope to be negatively associated with serious adverse events. The Evaluation of Guidelines in Syncope Study (EGSYS) score, developed to identify patients with cardiac syncope, reported a similar finding.…”
Section: Discussionmentioning
confidence: 69%
“…1 We then used the results of a previous retrospective analysis of this patient population to estimate the percentage of these visits that are intermediate-risk, justifying the need for further hospitalization following the initial ED evaluation, but also not clearly requiring inpatient admission. 20 Previous studies show that older patients presenting to the ED with syncope are hospitalized at high rates, approaching 90%, 21,22 so we proceeded with the basic assumption that the intermediate-risk cohort requires hospitalization.…”
Section: Main Modelmentioning
confidence: 99%
“…There was no anemia in the patients who died within 30 days and we found no effect of anemia on the development of severe events in our study. (10). The fact that a severe event developed in only two of our patients and that these two patients were hospitalized shows that we evaluated the risk criteria in these patients correctly.…”
Section: Resultsmentioning
confidence: 99%